What does the pronunciation of plosives and fricatives by Chinese learners of Portuguese teach us? - Castelo, Adelina (2021)
Producing didactic materials for teaching the Portuguese pronunciation to Chinese learners should take into account their specific difficulties. Consequently, defining the phonetic-phonological profile of these learners is one of the important tasks to be accomplished, and for this purpose a study based on the oral production data of plosives and fricatives is still in need. The aim of the present study is: (i) to identify the problems faced by the Chinese learners of Portuguese in the pronunciation of plosives and fricatives; (ii) to draw the didactic implications for the teaching of pronunciation. Eight native speakers of Mandarin Chinese were asked to name orally pictured objects. The words included in the corpus were controlled for some linguistic variables (e.g. stress position) and included one of the twelve obstruent consonants in standard European Portuguese. The results are analyzed in terms of (i) the impact of linguistic variables on the success rate and (ii) the reconstruction strategies for non-target productions. An important finding is the existence of significantly more difficulties with voiced plosives. Finally, the contributions to the definition of the phonetic-phonological profile of Chinese learners of Portuguese and to these consonants’ pronunciation teaching are systematized.